Directly investigating the interaction between aptamers and thrombin by atomic force microscopy1. Issue 12 (11th November 2013) - Jiao, Fang; Fan, Huajun; Yang, Guangda; Zhang, Fan; He, Pingang
<x xml:space="preserve">Abstract</x> Aptamers are single‐stranded nucleic acid molecules that can be used for protein recognition, detection, and inhibition. Over the past decades, two thrombin‐binding aptamers (15apt and 27apt) were reported by systemic evolution of ligands by exponential enrichment technique. Though many studies have been reported about the interactions between the aptamers and thrombin by atomic force microscopy, the thrombins in those studies were all immobilized by chemical agents. Recently, we developed a new method using atomic force microscopy to directly investigate the specific interactions between thrombin and its two aptamers without immobilizing the thrombin. Furthermore, the unbinding dynamics and dissociation energy landscapes of aptamer/thrombin were discussed. The results indicate that the underlying interaction mechanisms of thrombin with its two aptamers will be similar despite that the structures of 15apt and 27apt are different in buffer solution. Copyright © 2013 John Wiley & Sons, Ltd.